ANALISIS PENDAPATAN MASYARAKAT DALAM PEMANFAATAN HUTAN TEMBAWANG DI DUSUN KURNIA KECAMATAN KUALA BEHE KABUPATEN LANDAK Analysis of Public Income in the Utilization of Forest Tembawang in the Village Kurnia District Kuala Behe, Landak Regency - Dedi, Wihelmus; Surachman, Maman; rizal, Fah (JURNAL HUTAN LESTARI, 2015)
ABSTRAK This study aims to determine the level of income of the people in forest tembawang use in village to Kurnia of District of Kuala Behe Landak Regency. The study was conducted by direct interview by census (100%), respondents as many as 113 family based on population (KK). The overall result of tembawang forest products and forest products revenue outside tembawang shows people's income from outside employment a result of forest tembawang Rp 1,886,681, - / month or 62.14890% of the total revenue with the highest income variation of Rp 15.575 million, - / month and the lowest revenue of Rp 425.000, - / month. While income from forest products tembawang contributed 37.8510% of the total income of society. income of farmers in forest tembawang by 40%, while 60% is influenced by other factors such as weather factors mileage and prices are constantly changing market. Kata kunci : income community, tembawang forest, kurnia village